Peningkatan Kapasitas Produksi dan Pemasaran Kelompok Budi Daya Ikan Candi Madani Kelurahan Candiroto Kecamatan Kendal Kabupaten Kendal - Sulaiman Kurdi; Umi Hani; Novita Triyatun (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
The Candi Madani fish farming group in Candiroto Urban Village, Kendal District, Kendal Regency has productive economic potential in freshwater aquaculture. However, the group still faces several challenges related to production management, feed efficiency, business recording, water quality control, and marketing of harvested fish. This community service program aimed to improve the group’s production and marketing capacity through technical aquaculture training, business management assistance, production cost recording, and simple digital marketing optimization. The program applied a participatory approach consisting of needs assessment, training, field practice, mentoring, and evaluation through pre-test and post-test instruments. The results indicate an increase in participants’ understanding of production management from an average score of 56.40 to 84.20, and marketing understanding from 52.80 to 82.60. The program also encouraged the group to apply basic business records and promote fish products through social media and WhatsApp Business. Furthermore, the mentoring process helped the group formulate production planning based on harvest cycles, local market segmentation, and direct marketing strategies targeting consumers, food stalls, and community networks. This program demonstrates that strengthening fish farming groups should be conducted in an integrated manner, covering not only technical production aspects but also business management and marketing capacity to improve group independence, productivity, and competitiveness. Keywords: fish farming; production capacity; digital marketing; business group; community service